How to work with children and animals: A guide for school‐based citizen science in wildlife research. (12th November 2019) - Soanes, Kylie; Cranney, Kate; Dade, Marie C.; Edwards, Amy M.; Palavalli‐Nettimi, Ravindra; Doherty, Tim S.
Abstract: Engaging school students in wildlife research through citizen science projects can be a win–win for scientists and educators. Not only does it provide a way for scientists to gather new data, but it can also contribute to science education and help younger generations become more environmentally aware. However, wildlife research can be challenging in the best of circumstances, and there are few guidelines available to help scientists create successful citizen science projects for school students. This paper explores the opportunities and challenges faced when developing school‐based citizen science projects in wildlife research by synthesising two sources of information. First, we conducted a small, school‐based citizen science project that investigated the effects of supplementary feeding on urban birds as a case study. Second, we reviewed the literature to develop a database of school‐based citizen science projects that address questions in wildlife ecology and conservation. Based on these activities, we present five lessons for scientists considering a school‐based citizen science project. Overall, we found that school‐based citizen science projects must be carefully designed to ensure reliable data are collected, students remain engaged, and the project is achievable under the logistical constraints presented by conducting wildlife research in a school environment. Ultimately, we conclude that school‐based citizen science projects can be a powerful way of collecting wildlife data while also contributing to the education and development of environmentally aware students.